2002
DOI: 10.1126/science.298.5599.1790
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation in Campylobacter jejuni and Its Functional Transfer into E. coli

Abstract: N-linked protein glycosylation is the most abundant posttranslation modification of secretory proteins in eukaryotes. A wide range of functions are attributed to glycan structures covalently linked to asparagine residues within the asparagine-X-serine/threonine consensus sequence (Asn-Xaa-Ser/Thr). We found an N-linked glycosylation system in the bacterium Campylobacter jejuni and demonstrate that a functional N-linked glycosylation pathway could be transferred into Escherichia coli. Although the bacterial N-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
721
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 723 publications
(753 citation statements)
references
References 20 publications
22
721
0
10
Order By: Relevance
“…In another neoglycoprotein production experiment, ssPelB and ssTorA were successfully used for the transfer of the N-glycosylation target protein AcrA of C. jejuni to the periplasm of E. coli, demonstrating that bacterial N-glycosylation can occur independently of the protein translocation machinery. [21,29] Concerning periplasmic targeting of S-layer proteins in general, MBP has been reported to export the S-layer protein SbsA of G. stearothermophilus PV/72 to the periplasm of E. coli. [32] The different S-layer fusion proteins were expressed in E. coli BL21 Star (DE3) carrying the respective expression plasmids.…”
Section: Periplasmic Targeting Of Sgsementioning
confidence: 99%
See 3 more Smart Citations
“…In another neoglycoprotein production experiment, ssPelB and ssTorA were successfully used for the transfer of the N-glycosylation target protein AcrA of C. jejuni to the periplasm of E. coli, demonstrating that bacterial N-glycosylation can occur independently of the protein translocation machinery. [21,29] Concerning periplasmic targeting of S-layer proteins in general, MBP has been reported to export the S-layer protein SbsA of G. stearothermophilus PV/72 to the periplasm of E. coli. [32] The different S-layer fusion proteins were expressed in E. coli BL21 Star (DE3) carrying the respective expression plasmids.…”
Section: Periplasmic Targeting Of Sgsementioning
confidence: 99%
“…For this purpose, the plasmid pACYCpgl harboring the complete pgl gene cluster of C. jejuni that is responsible for heptasaccharide biosynthesis and its transfer to the protein was transformed into E. coli BL21 Star (DE3). [21] As a positive control, to confirm that the glycosylation machinery of C. jejuni functions under the chosen conditions, the plasmid pEC(AcrA-per), expressing periplasmic soluble AcrA of C. jejuni with the PelB signal peptide and a Cterminal hexahistidine tag, was transferred to electrocompetent E. coli BL21 Star (DE3) cells containing pACYCpgl. [29] Analysis of the expression product by Western immunoblotting, using a heptasaccharide specific antibody (anti-pgl antibody), confirmed glycosylation of AcrA ( Figure 3, lane 8).…”
Section: Design Of An Sgse Neoglycoprotein Carrying a C Jejuni Heptamentioning
confidence: 99%
See 2 more Smart Citations
“…14 Intriguingly, it has been shown that the glycosylation machinery can be transferred to E. coli , resulting in E. coli cells capable of N-glycosylation of proteins. 4143 Introduction of this machinery into E. coli SHuffle cells may enable the production of N-glycosylated antibodies. Such an improvement would afford a mAb more similar to its mammalian-expressed therapeutic counterpart.…”
Section: Discussionmentioning
confidence: 99%